THE IMPLEMENTATION OF INQUIRY-BASED LEARNING IN TEACHING ENGLISH AT SMP NEGERI 1 GEMOLONG IN 2015/2016 ACADEMIC YEAR - Lestari, Endang (JoLLIET, 2016)
This is a naturalistic qualitative research, which aims to describe and toexplain the implementation of Inquiry-based Learning in teaching English atSMP negeri 1 Gemolong consisting the component of teaching learningnamely; learning objective, classroom procedure, classroom technique, therole of instructional material, teacherâs role, studentsâ role, media,assessment. The researcher used observation, interview and document in collecting the data. Based on the research findings, the researcher found the results as follows; 1) there are two kinds of learning objectives, namelygeneral learning objectives and specific learning objectives, 2) classroomprocedure used exploration, elaboration, confirmation, 3) classroomtechnique used in teaching English were identifying key words, reading text,discussion, role playing, comprehension, crazy story games, 4) the roles ofinstructional materials were as a reference source for learners on grammar,vocabulary, pronunciation; as a source of stimulation and ideas forclassroom activities, 5) English teacher had roles as facilitator, manager,explainer, motivator, 6) studentsâ roles were students learning from teacher,students learn from other students, students as subject of learning, studentsas performer, 7) media used in teaching English were video, drama, board,text, and 8) assessment used by teacher were test and non-test, test wasdivided into daily test, mid test, final test. Non-test was divided into everyskill in teaching learning process.Key words: inquiry-based learning, teaching English